Answer:
(p ∧ q)’ ≡ p’ ∨ q’
Step-by-step explanation:
First, p and q have just four (4) possibilities, p∧q is true (t) when p and q are both t.
p ∧ q
t t t
t f f
f f t
f f f
next step is getting the opposite
(p∧q)'
<em>f</em>
<em> t</em>
<em> t</em>
<em> t</em>
Then we get p' V q', V is true (t) when the first or the second is true.
p' V q'
f <em>f</em> f
f <em>t</em> t
t <em>t</em> f
t <em>t</em> t
Let's compare them, ≡ is true if the first is equal to the second one.
(p∧q)' ≡ (p' V q')
<em>f f </em>
<em> t t</em>
<em> t t</em>
<em> t t</em>
Both are true, so
(p ∧ q)’ ≡ p’ ∨ q’
To solve for y, isolate the variable to one side.
9x+3y=4
-9x -9x
~~~~~~~~
3y= -9x+4
~~~~~~~~
3y= -9x+4 (Divide both sides by 3)
y=-3x+4
Multiply the exponent of x by 4giving <span> The answer is </span><span> x^4 evaluates to </span><span> Multiply and 5 </span><span> Multiply and 1 </span><span> The just gets copied along. </span><span> The answer is </span> <span> 5*x^4 evaluates to </span><span> Multiply the exponent of x by 4giving </span><span> The answer is </span><span> x^4 evaluates to </span><span> Multiply and 6 </span><span> Multiply and 1 </span><span> The just gets copied along. </span><span> The answer is </span> <span> 6*x^4 evaluates to </span><span> Multiply the exponent of x by 2giving </span><span> The answer is </span><span> x^2 evaluates to </span><span> Multiply and 3 </span><span> Multiply and 1 </span><span> The just gets copied along. </span><span> The answer is </span> <span> 3*x^2 evaluates to </span><span> 6*x^4-3*x^2 evaluates to </span><span> The answer is </span><span> 6*x^4-3*x^2+7 evaluates to </span><span> Multiply by </span><span> we multiply by each term in term by term. </span> This is the distributive property of multiplication. <span> Multiply and </span><span> Multiply the and </span><span> Multiply and </span><span> Combine the and by adding the exponents, and keeping the x, to get </span><span> The answer is </span> <span> × = </span><span> Multiply and </span><span> Multiply the and </span><span> Multiply and </span><span> Combine the and by adding the exponents, and keeping the x, to get </span><span> The answer is </span> <span> × = </span><span> Multiply and 7 </span><span> Multiply and 1 </span><span> The just gets copied along. </span><span> The answer is </span> <span> × 7 = </span><span> 5*x^4*(6*x^4-3*x^2+7) evaluates to </span><span>The final answer is </span>
Answer:
-2s
Step-by-step explanation:
2s+(-4s)
2s-4s
-2s
Hope this helps ;) ❤❤❤
Answer:
uwiouwj22nnjj n2k2k2km n2n2j2j2j2jn2n2 2 2 2 2n2j2j2n2n2 2 2 3 3n2j2j2n3n<u> </u><u>n</u><u>3</u><u>j</u><u>3</u><u>n</u><u>3</u><u>n</u><u>3</u><u>n</u><u>3</u><u> </u><u>3</u>